ENDOFTALMITIS - Hondrizal Hondrizal (Yayasan Nusantara Hasana Berdikari, 2026)
Endophthalmitis is a severe intraocular inflammatory condition caused by microbial infection involving the vitreous and aqueous humor, which may lead to significant visual impairment or blindness if not treated promptly. This condition can occur as a result of postoperative complications, ocular trauma, endogenous hematogenous spread, or extension of adjacent ocular infections. The most common causative organisms include Gram-positive bacteria, Gram-negative bacteria, and fungi. Clinical manifestations typically include decreased visual acuity, ocular pain, redness, photophobia, hypopyon, and vitreous inflammation. Diagnosis is established through clinical examination supported by microbiological analysis of vitreous or aqueous samples. Early recognition and prompt management are essential to preserve visual function. Treatment commonly involves intravitreal antibiotic or antifungal injections, systemic antimicrobial therapy, and pars plana vitrectomy in severe cases. Prognosis depends on the causative organism, severity at presentation, and timeliness of intervention. Comprehensive management and early diagnosis significantly improve visual outcomes and reduce complications associated with endophthalmitis.